Cavitation phenomenon in penetration of rigid projectiles into elastic-plastic targets. (May 2021) - Feldgun, V.R.; Yankelevsky, D.Z.; Karinski, Y.S.
Highlights: Cavitation during penetration of rigid projectiles into elastic-plastic targets is studied. An analytical criterion for projectile-target separation is developed. Formulae for the cavitation critical velocity VCR and contact zone size x* are obtained. Penetration of ogive and Rankine ovoid nose projectiles into aluminum targets are investigated. The effect of projectile and medium properties on VCR and on x* are studied. Abstract: This paper presents an analytical study on the cavitation phenomenon during penetration of a rigid projectile into an elastic-plastic target. The developed analytical approach is based on the general solution of the quasi-static and non-stationary dynamic cylindrical/spherical cavity expansion problem with assigned kinematic boundary condition at the cavity boundary (variable, time dependent radial velocity). An analytical projectile-target separation criterion is developed for a projectile having an arbitrary shape and for a target described by a simplified material model with a locked equation of state and a linear shear failure relationship. This relatively simple model may represent the behavior of different materials reasonably well yet allow an analytical solution of the problem. The paper derives the analytical expression of the contact zone size using both the cylindrical and spherical cavity expansion approaches and presents the related normal contact stresses acting on the projectile nose surface that maintains contact with the target. Examples of the developed formulation is presented for ogive nose and Rankine ovoid projectiles hitting aluminum targets, with a constant shear failure envelope, at different velocities and comparisons with known analytical and numerical solutions are shown. The effect of projectile and medium properties on the size of the contact zone are studied.